Human Infecting Parasitic Worms, In Cockroaches from Odau in the Niger Delta Region of Nigeria - Okafor-Elenwo, E. J; Elenwo, A. C (International Journal of Natural Sciences Research, 2014)
Parasitic worms of difference species were obtained from cockroaches examined in Odau, a community in the Niger Delta region of Nigeria. One thousand (1000) cockroaches were caught from households (one hundred), randomly selected within the community. The helminths were identified as Trichuris trichuria.(N=313; 2O.6%); Ancylostoma duodenale (N=368; 24.4); Ascaris lumbricoides (N=571;36.6%); Strongylloides stecoralis(N=173;11.4%); and Trichostrongylous sp.(N=93; 6.1%). Seven hundred and ninety one (79.1%) out of the cockroaches, had parasitic helminths. The total number of parasites isolated was one thousand, five hundred and eighteen (1,518). The rate of occurrence of Ascaris sp. in the cockroaches was significantly higher (p<0.05) compare to the other parasites. The abundance of helminth parasitic species in the cockroaches examined in the present study indicate that the environment may not be in good sanitary condition. If this level of association between cockroaches and helminth parasites is maintained, the transmission of parasitic agents/diseases especially to humans in the area will increase.